(untitled) (ArtCultura, 2009)
O objetivo central deste artigo será o enfoque da rede alegórica tramada por Antônio Vieira para configurar a infinitude do útero de Maria no "Sermão de Nossa Senhora do Óâ€?. Esse sermão recicla um procedimento retórico-poético bastante comum no século XVII, fundamentado na manipulação de particularidades do desenho de uma letra; no caso, o o remete iconicamente a uma realidade - o útero -, a qual remete a um sentido alegórico: não tendo princípio nem fim a figura circular, o o e o útero se identificam como representações da eternidade. Assim, desdobra-se agudamente no texto o seguinte paradoxo: como o corpo finito da Virgem pode conter em si o espaço inteiro do mistério e do infinito. Abordaremos também as noções de similitude e de participação, inerentes à metafísica cristã, que fundamentam essa rede de alegorias engenhosamente tecida por Antonio Vieira. PALAVRAS-CHAVE: Antônio Vieira; oratória sacra; encarnação; Uterus Mariae; alegoria. ABSTRACT: This article focuses on the allegorical net created by Antonio Vieira in his configuration of Maria’s uterus in the work "Sermão de Nossa Senhora do Óâ€?. This sermon retakes a rhetoricaland poetical procedure that was very usual in the seventeenth century, based on the manipulation of some specific peculiarities of the design of one letter from the lphabet. In the case of the referred sermon, the letter o is linked, in an iconic way, to one reality - the uterus -, that also refers to an allegorical meaning: considering that any circular figure does not have neither beginning nor ending, the o and the uterus are both identified as representations of eternity. So, the text develops the following paradox: how can the Virgin’s finite body enclosure in itself the whole space of mystery and infinity? The analysis will also consider the concepts of similitude and participation, belonging to Christian metaphysics, which are the basis of this chain of allegories ingeniously knitted by Vieira. KEYWORDS: Antônio Vieira; sacred oratory; incarnation; Uterus Mariae; allegory.